Sistem Pendukung Keputusan pada Penjurusan Siswa Terkendala dengan metode Analytic Hierarchy Process - Antonius Agung Hartono (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
The Student concentration selection is an alternative to develop each student based on his academic skill and interest. The selection is conducted by observing the completion of passing grade scores on certain courses that are associated with certain concentration and by taking account the concentration preference picked by each student. Concentration selection for constrained students are based on good grades of respective student on a certain concentration program. However, it often happens that concentration selection for constrained students is conducted without looking at his/her good grades. This research aims to develop a DSS (Decision Support System) application on concentration selection for constrained students. The proposed DSS is developed by implementing Analytic Hierarchy Process (AHP). The testing is undertaken by comparing the result of concentration selection for constrained students done in manual way and the result obtained by developed DSS implementing AHP. For the purpose of testing, data of constrained students from X-G class of 2010/2011 school period was used. The comparison result proves that AHP in the developed DSS works well and right.